Factors Affecting Study Program Selection: A Comprehensive Study of Student Decision-Making in North Maluku Universities - Muhammad Sofyan Do Musa; Budiyanto Budiyanto; Suhermin Suhermin (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
It is essential to understand and address the evolving factors influencing student decision-making in choosing study programs at universities in North Maluku to provide valuable insights for educational institutions. This research aims to analyze the factors influencing student decision-making in choosing a study program at universities in North Maluku, with a specific focus on the mediation role of psychological factors in the decision-making process. This research uses purposive sampling to acquire the data. A total of 219 respondents were acquired and analyzed using SEM. Socio-cultural has a positive and insignificant effect on psychology. The referral group has a negative and insignificant effect on psychology. Marketing communications have a negative and insignificant effect on psychology. Personal factors have a positive and significant influence on psychology. Socio-cultural factors have a negative and insignificant effect on decision-making. The referral group has a negative and insignificant effect on decision-making. Marketing communications have a positive and insignificant effect on decision-making. Personal factors have a positive and insignificant effect on decision-making. Psychology has a positive and significant influence on decision-making. Psychology mediates socio-cultural influences on decision-making. Psychology mediates the influence of reference groups on decision-making. Psychology does not mediate the influence of marketing communications on decision-making. Psychology mediates the influence of personal factors on students' decision-making.